PENGARUH EFEKTIFITAS E-TICKETING DAN PROMOSI ON-LINE TERHADAP PENINGKATAN VOLUME PENJUALAN PT. CITILINK INDONESIA DI BANDARA HALIM PERDANAKUSUMA - Yanthy Yosepha, Sri; Diah Pitaloka, Galuh (JURNAL ILMIAH M-PROGRESS, 2017)
Citilink is one of the Low Cost Carrier airlines in Indonesia, providing customers with options for cheap and quality flights that make it easier for customers to reach their destination. But With the rapid increase of the air transport industry nowadays that have implemented internet service in marketing strategy such as e-ticketing and promotion online make the competition between companies more tight in grabbing customers and maintaining existing market share. Citilink is one airline service company since 2012 has implemented e-ticketing and online promotion to achieve sales volume increase target. The e-ticketing and online promotion system is a marketing strategy that brings marketers and consumers closer together, the ease of consumers to interact effectively and efficiently at the end of the consumer's benefit and then repurchase and recommend to friends, relatives and family to buy and use information interactive through online facilities. Based on this background, the formulation of the problem This study aims to determine (1) is there any effect of e-Ticketing effectiveness partially on the increase of sales volume, (2) is there any influence of partial online promotion on sales volume increase, (3) is there any effect of e- and simultaneous online promotion of increased sales volume. The method used is accumulated sampling with 100 respondents using Citilink at Halim Perdanakusuma Airport. The results obtained by multiple linear regression equation is Y = 0.909 + 0.404X1 + 0.101X2, indicating that the Effectiveness of E-ticketing and online promotion have a positive and significant impact on the increase of sales volume. Partial test (t test) e-ticketing effectiveness is Y1 = 3.435 + 0.513X1 shows that Effectiveness of E-ticketing have a positive and significant impact to the increase of sales volume. Partial test (t test) online promotion is Y1 = 5.719 + 0.329X2. shows that online promotion has a positive and significant impact on sales volume increase. Keywords: effectiveness of e-ticketing, online promotion, increase in sales volume